2008
DOI: 10.1080/10519990802442405
|View full text |Cite
|
Sign up to set email alerts
|

Plasma characterization for nitridation of aluminium alloy using 50 Hz ac discharge

Abstract: A 50 Hz ac abnormal glow discharge is characterized as a function of filling pressure (1-4 mbar) using a Langmuir probe. It is found that electron temperature, electron density and electron energy distribution function decrease with the gas filling pressure. Nitriding of aluminum alloy (Al−Mg 2 −Si) is performed for various time durations (3, 6, 9 and 12 h) and pressures (1 and 2 mbar) by keeping the input power (100 W) and substrate temperature (250 • C) constant. To explore the surface properties induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Nitriding for longer durations supplies more nitrogen and results in the formation of more molybdenum nitride and hence denser layers, resulting in enhanced packing density. [27] Hence it is concluded that the nitrogen supply to the modified surface layer of molybdenum is enhanced with increased nitriding time, due to which molybdenum nitride concentration at the surface is enhanced, resulting in the formation of more compact pore-free films for longer nitriding (10 h) duration. Figures 6(a)-6(c) show the surface morphology of the plasma-nitrided specimens for 2 mbar and 3 mbar fill gas pressures.…”
Section: Sem Analysismentioning
confidence: 99%
“…Nitriding for longer durations supplies more nitrogen and results in the formation of more molybdenum nitride and hence denser layers, resulting in enhanced packing density. [27] Hence it is concluded that the nitrogen supply to the modified surface layer of molybdenum is enhanced with increased nitriding time, due to which molybdenum nitride concentration at the surface is enhanced, resulting in the formation of more compact pore-free films for longer nitriding (10 h) duration. Figures 6(a)-6(c) show the surface morphology of the plasma-nitrided specimens for 2 mbar and 3 mbar fill gas pressures.…”
Section: Sem Analysismentioning
confidence: 99%
“…The thickness of nitride layer is approximately 4 µm for a treating duration of 4 h, and increases to 14 µm for a nitriding treatment of 12 h. At a helium concentration of 40%, the thickness of nitride layer is 11.2 µm and at a helium concentration of 50% it is about 12 µm. It is found that the growth of nitride layer takes place mainly by the diffusion of nitrogen [55] .…”
Section: Surface Morphologymentioning
confidence: 99%